2008
DOI: 10.1111/j.1749-4486.2008.01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of vestibular schwannomas: third review of a 10‐year prospective study

Abstract: Seventy-two patients with a unilateral vestibular schwannoma have been treated conservatively for a median of 121 months. They have been followed prospectively by serial clinical examination, MRI scans and audiometry. Twenty-five patients (35%, 95% CI: 24-47) failed conservative management and required active intervention during the study. No factors predictive of tumour growth or failure of conservative management could be identified. Seventy-five per cent of failures occurred in the first half of the 10-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
116
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 7 publications
14
116
0
1
Order By: Relevance
“…38,39,75,101 This obviously does not account for patients who develop hearing loss without any significant tumor growth (as described earlier in this paper).…”
Section: Hypothetical Casementioning
confidence: 99%
See 4 more Smart Citations
“…38,39,75,101 This obviously does not account for patients who develop hearing loss without any significant tumor growth (as described earlier in this paper).…”
Section: Hypothetical Casementioning
confidence: 99%
“…68 There are very few prospective studies that report tumor growth in the patients followed with observation. Régis et al 83 reported tumor growth in 77% of their patients (mean follow-up 5.3 years); Hajioff et al, 39 in their 10-year follow-up prospective study (median duration of follow-up 121 months), reported tumor growth in 78% of patients (< 1 mm/year in 38% and > 1 mm/year in 40%); and Stangerup et al 96 found that only 17% of intrameatal tumors became extrameatal and that only 28.9% of extrameatal tumors showed growth (mean follow-up 3.6 years). It is difficult to develop a scientific rationale that would explain this variation.…”
Section: Hypothetical Casementioning
confidence: 99%
See 3 more Smart Citations